1993
DOI: 10.1254/jjp.62.137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Heparin on the Inhibitory Activities of Human Urinary Trypsin Inhibitor (Ulinastatin) on Trypsin, Chymotrypsin and Leukocyte Elastase

Abstract: ABSTRACT-The inhibitory effects of emedastine difumarate on histamine release were studied in rat peritoneal mast cells. Emedastine significantly inhibited substance P (SP)-induced histamine release at con centrations above 10-9 M in the presence of extracellular Ca2+ and at concentrations above 10-" M in its absence. At concentrations of 10-8 M or higher, emedastine significantly inhibited SP-induced Ca" release from intracellular Ca stores and SP-induced 45Ca uptake into mast cells. Emedastine also inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A number of studies have demonstrated that several types of receptors, such as NK1 receptor, exist for SP (18). More recently, some antiallergic drugs have been suggested to possess a binding affinity for SP receptors (19). This raises the possibility that antiallergics occupy SP receptors in an antagonistic fashion, resulting in the elevation of circulating SP.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have demonstrated that several types of receptors, such as NK1 receptor, exist for SP (18). More recently, some antiallergic drugs have been suggested to possess a binding affinity for SP receptors (19). This raises the possibility that antiallergics occupy SP receptors in an antagonistic fashion, resulting in the elevation of circulating SP.…”
Section: Discussionmentioning
confidence: 99%
“…produced significant inhibition of passive peritoneal anaphylaxis in guinea-pigs, while ketotifen fumarate was ineffective even at 0.3 mg/kg, p.o. These results indicate that the clinical antiallergic effects of emedastine difumarate involved the inhibition of histamine release [57].…”
Section: Pharmacodynamicsmentioning
confidence: 72%
“…Emedastine is an H 1 antagonist and therefore affects the signs and symptoms initiated by histamine binding to the H 1 receptor. In preclinical studies, emedastine was extremely efficacious in inhibiting the histamine release (7) and eosinophil chemotaxis (8).…”
Section: Discussionmentioning
confidence: 99%